2019
DOI: 10.21608/jabps.2019.6766.1031
|View full text |Cite
|
Sign up to set email alerts
|

Two smart spectrophotometric methods for simultaneous determination of Lisinopril and Hydrochlorothiazide in binary mixtures

Abstract: Two new, simple, fast and sensitive spectrophotometric methods were developed for analysis of binary mixtures of Lisinopril (LIS) and hydrochlorothiazide (HCT). These methods were absorptivity factor method and ratio subtraction method. In the first method, calculations were made using the absorbance of the mixtures at 211 nm where LIS absorptivity is half HCT absorptivity. On the other hand, the second method was based on obtaining the original spectrum of LIS from the zero order spectrum of the binary mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…2.2 Method II: Ratio subtraction method [11][12][13] This method works well for a combination of two drugs A and B with overlapped spectra without the need of an ISP provided that one of them (B) has an extended part in its spectrum of zero order with no interference from drug A. The concentration of drug A can be determined using ratio subtraction where the zero-order spectrum of the mixture is divided by the zero-order spectrum of a certain concentration of B named as the divisor (B').…”
Section: Methodsmentioning
confidence: 99%
“…2.2 Method II: Ratio subtraction method [11][12][13] This method works well for a combination of two drugs A and B with overlapped spectra without the need of an ISP provided that one of them (B) has an extended part in its spectrum of zero order with no interference from drug A. The concentration of drug A can be determined using ratio subtraction where the zero-order spectrum of the mixture is divided by the zero-order spectrum of a certain concentration of B named as the divisor (B').…”
Section: Methodsmentioning
confidence: 99%
“…Also, a modern approach of HPLC 25 utilizing a Photo Diode Array detector (HPLC-PDA) was utilized for the simultaneous estimation. The absorptivity factor method and ratio subtraction method are the two new smart spectrophotometric methods 26 used for the estimation of Hydrochlorothiazide. From the exhaustive literature survey, it was found that little work on the HPTLC method has been reported for the simultaneous estimation of Ramipril and Hydrochlorothiazide in the combined formulation.…”
Section: Fig 2: Structure Of Hydrochlorothiazidementioning
confidence: 99%
“…HZ is excreted (>95%) as unchanged drug in urine [23,24]. Different techniques have been reported for HZ quantitation such as HPLC [25][26][27][28], GC [29], spectrophotometry [30,31], and voltammetry [32].…”
Section: Introductionmentioning
confidence: 99%